Actual Problems of Corpus Delicti of the Crime on the Creation, Organization and Management of Pyramid Schemes - Hovhannisyan, Arman; Petrosyan, Levon (Bulletin of Yerevan University C: Jurisprudence, 2021)
Within the framework of this article, the crime of creating, organizing or managing a financial pyramid has been studied in detail. Analyzing the crime in the light of foreign regulations, practical cases and the draft Criminal Code of the Republic of Armenia, a number of shortcomings related to the article were revealed, the solution of which can result in making the article applicable in reality, giving adequate qualifications to many publicly dangerous situations.